Study on Axial Fatigue Performance and Life Prediction of High-Strength Bolts at Low Temperatures - Liang Zhang; Guoqing Wang; Xuanzhe Ji; Shujia Zhang; Honggang Lei (Buildings)
High-strength bolts are widely used in outdoor steel structures such as transmission towers and bridges, where they not only endure cyclic wind loads and vehicle loads but also frequently operate in low-temperature environments. However, there is limited research on the axial fatigue performance of high-strength bolts, particularly regarding their mechanical behavior at low temperatures. Therefore, this study conducted a series of fatigue tests on high-strength bolts at 20 °C and 0 °C, both with and without pretension. We established S-N curves and fatigue limits for the three scenarios, revealing that pretension significantly enhances the fatigue life of the bolts, with a 10% increase in fatigue limit at 0 °C compared to 20 °C. However, due to the influence of pretension, the external load has a minimal effect on the actual stress experienced by the bolts, resulting in S-N curves for bolts with pretension being very similar to those for bolts without pretension during cyclic loading. Additionally, we obtained the load–displacement curves and corresponding stiffness degradation patterns of the bolts at both temperatures, finding that all bolts exhibited significant stiffness degradation after reaching 0.8 times their fatigue life. The high-strength bolts at 0 °C demonstrated greater stiffness and faster crack propagation rates, with increases of approximately 6% and 8%, respectively. Furthermore, electron microscope scans were used to clarify the fatigue crack initiation and the evolution of fatigue striations at both temperatures. Finally, by combining refined numerical simulations with the local stress–strain method, the effectiveness of the local stress–strain method for evaluating the fatigue life of bolts without pretension was validated. Building on this, we extended the method to bolts at 0 °C and those subjected to pretension, recommending notch sizes of 0.4 mm and 1.1 mm for fatigue life assessment of bolts with pretension at 0 °C and 20 °C, respectively.